(untitled) (Window of Public Health Journal, 2025)
Based on the 2020 Indonesian Health Profile data, it was found that infectious diseases contributed to death in the group of children aged 29 days to 11 months. The purpose of this study was to analyze Pneumonia Incidents Based on Socio-Cultural Interventions in Reducing Infant Mortality Rates in Pangkep Regency (Case Study at the Community Health Center with the Highest Cases of Pneumonia). This type of research employs qualitative methods and is characterized by descriptive approaches. The data collection techniques employed were observation, in-depth interviews, and review of documents from the Baring Community Health Center in Pangkep Regency. Informants in this study were 6 people consisting of 1 key informant, 2 regular informants and 3 supporting informants. Data analysis was carried out by means of in-depth interviews, observation, and documentation. Qualitative data is presented in narrative form and forms a matrix. From the results of the study, it was found that the Analysis of pneumonia incidents based on socio-cultural interventions in the community health center with the highest cases of pneumonia in terms of Socio-Cultural, Environmental, Maternal Characteristics and Infant Characteristics was not good enough but was running optimally and still needed to improve health promotion. It is recommended that the Community Health Center increase educational and counseling activities about pneumonia.